Finite Element Analysis of Bus Rollover Test in Accordance with UN ECE R66 Standard - Wicaksono, Satrio; Faisal Rahman, M. Rizka; Mihradi, Sandro; Prifiharni, Siska (ITB Journal Publisher, LPPM ITB, 2017)
Bus transportation plays a significant role in short and long distance mass transportation in Indonesia. The number of buses in Indonesia shows significant growth every year. However, there is a lack of regulations regarding bus construction safety and the increasing number of bus accidents is also becoming a major concern. In this paper, a computer simulation of bus rollover is presented. The bus structure was modeled to represent the mass distribution in a real bus. Two conditions were tested: the bus when empty and when fully loaded. Both the empty bus and fully loaded bus simulation results show that the bus did not comply with the UN ECE R66 safety standard. The results were validated by making a comparison with other tests that have been conducted by other researchers.